IMPLEMENTASI PROGRAM PEMANFAATAN LIMBAH KOTORAN SAPI UNTUK PEMBUATAN BIOGAS SEBAGAI UPAYA KETAHAN ENERGI DI DESA SODONG KECAMATAN SAKETI KABUPATEN PANDEGLANG - Siti Julaeha Siti Julaeha; Jumanah Jumanah (NIAGARA Scientific Journal, 2018)
This research is based on indications of problems in the field including: (1) insufficient understand the benefits of biogas, (2) inadequate human resources, (3) quality results of waste utilization are still lacking, (4) Inadequate facilities and infrastructure, (5) Lack of socialization of waste utilization resulting in community participation still low. The purpose of this research is to determine program implementation utilization of cow dung waste as an energy security effort. This research method with a qualitative approach, using primary and secondary data sources. Adpun Informants in research are beneficiaries, groups and parties government. This research uses Grindel and Mazmanian Sabatier theories including dimensions; (1) Influencing interests, (2) Type of benefit, (3) Degree changes to be achieved, (4) Location of decision making, (5) Program implementers, (6) Resources used, (7) Public support. The results of this study shows the implementation of a program for utilizing cow dung waste into biogas as an energy security effort, this can be seen from several things that are in accordance with The implementation theory that researchers use is the Mazmanian Sabatier and Grindle theories namely the types of benefits produced have not been maximally utilized by the community using the benefits of biogas are not all good from biogas or fertilizer the slurry. Judging from the indicators of the resources used, one of them is lacking human resources that have not really been trained to be able to utilize biogas and taking care of cattle because they are used to raising buffalo. And Public support, namely seeing whether the community supports or complies with the program this looks at the fact that the community is lacking, there are very few people who still survive using biogas even the group that has become the implementing agency has started not using biogas because people are still used to using it firewood is also familiar with the practical program.